The Iraqi public's uses of video journalism and the satisfaction achieved from it - Dr. Ahmed Abed Hussein (Genius Journals, 2024)
The Iraqi press was affected by many phenomena and developments that greatly changed the form and content of journalistic practices. Electronic journalism has produced a new communication technology known as video journalism. The study aimed to know the uses of the Iraqi public and the satisfactions achieved from that use based on the theory of uses and gratifications. The study included descriptive studies based on the media survey approach applied to a deliberate sample of the Iraqi public who used video journalism, which represented (400) individuals from 4 governorates in Iraq. The sample included the governorates of Baghdad, Erbil, Anbar, and Babylon, among those interested in and following the clips published about video journalism and specialized press websites from the period between December 1, 2022 to February 28, 2023 AD. The researcher used a questionnaire form with the aim of identifying the study sample’s uses of video journalism and knowing the motives for use and the satisfactions achieved
Keywords: Uses; satisfactions; Video Press